Effect of soil microstructure on the relationship between the intensity of nitrification and soil moisture - Studnicková, I (Folia microbiologica, 1979)
The relationship between the logarithm of nitrification intensity and moisture (expressed as pF) did not have an ideal linear course in structural soils in which pores of a certain size predominated. When increasing the incubation moisture it could be observed that the intensity of nitrification decreases at pF 3.5-4.4 and increases again on further increasing the incubation moisture. The detected anomaly was observed when applying moistures corresponding to peaks of derivation pF-curves. It can be assumed that the relationship between the intensity of nitrification and moisture is modified by soil microstructure; therefore, this relationship was studied in more detail in the present communication.
Keywords: Nitrates; půdní mikrobiologie; Nitrites; Water; Bacteria; půda; Soil; Soil Microbiology; Particle Size; voda; dusitany; dusičnany; velikost částic